Anhelos (wishes), ideas y el inconsciente freudiano: una conversación con Donald Levy - De la Puente Arbaiza, Carlos Alberto (2014)
In his book, Freud Among the Philosophers, professor Donald Levy challenges the epistemological critiques directed against psychoanalysis on the grounds that those critiques misunderstood what Freud called the unconscious. According to Levy, neither “wishes” nor “Ideas”, which are the target of repression, are linked to, or depend upon, action. The author of this article conversed with professor Levy about this defense of psychoanalytic theory and about the opinion, contrary to Levy´s, that mental contents linked to action are also part of the Freudian unconscious.